Culturally Tailoring a Patient Empowerment and Diabetes Education Curriculum for the African American Church. (October 2017) - Whitney, Eric; Kindred, Elijah; Pratt, Abdullah; O'Neal, Yolanda; Harrison, Rev. Chauncey P.; Peek, Monica E.
Purpose: The African American church has long been recognized as a valuable partner for health interventions in the community. While an extensive literature exists documenting the potential efficacy of diabetes education programs in church settings, there has yet to be an effort to leverage spiritual beliefs and practices to promote diabetes self-management and shared decision making within a faith-based framework that is culturally tailored to the African American church. The purpose of this article is to describe the translation of a clinic-based diabetes education program into faith-based education curriculum tailored for use in the African American church. Conclusions: Themes extracted from focus groups and input from a faith-based community partner provided a methodical and patient-informed foundation for culturally tailoring and piloting a diabetes self-management curriculum for the African American church setting. This study illustrates how spirituality can be incorporated into interventions to enhance health promotion and behavioral change among African Americans with diabetes. Participants in our study described how religious beliefs play an active role in many aspects of diabetes care, including self-management behaviors, coping strategies, and patient/provider communication. In addition, this intervention can serve as a model for the development of patient-centered health interventions.